Survey Of Women’s Futsal Sports Achievement Coaching On Sidoarjo Porprov 2021 Team - Faiza, Nurul; I Putu , Panca Adi; I Made , Satyawan (Universitas Pendidikan Ganesha, 2024)
This research aims to find out the system of building performance on the Porprov futsal team daughter of the year 2021 district of Sidoarjo. The population in this study is the builder, manager, coach and 17 players of the Porprov futsal team daughter Sidoarjo district. The method used in this research is a survey with a type of qualitative research descriptive approach. Data collection methods in this study with interviews, observations and documentation are then analyzed using millies and huberman models in moleong. The results of this study show that the construction system of the porprov futsal team of the daughter of Sidoarjo district can already be categorized well according to the results of the observation indicators already carried out by the researchers. Among them are: 1. The system of implementation of the construction of the Porprov Futsal Team Princess District of Sidoarjo by starting to recruit players as talent scouting to the schools in Siroarjo as well as the girls' futsal clubs in Sinoarjo to see the seeds of athletes. 2. The organizational structure implemented in the Porprov Futsal Team Princess District of Sidoarjo has been formed itself ranging from the head coach, assistant, goal coach, massage, and sponsor manager all have their respective responsibilities and duties. 3. The training program applied in the construction of futsal sports on the Porprov Futsal Team Princess Sidoarjo district according to his headcoach always perform evaluation and more emphasizing physical than each of his players. to improve the mentality and skill of his team more hold tests. Recommendation to the organization's master to improve training in a consistent manner from an early age, advice to the manager of the Porprov futsal daughter team of Sidoarjo district to maintain good cooperative relations with various parties, advice for athletes to better maintain consistency in practice and advice to coaches to improve understanding to the entire player of the team of Porprov Futsal girl Sidoarjo district.